2003
DOI: 10.1255/ejms.578
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Ion—Molecule Reactions of Anabolic-Type Steroid Tertiary Alcohols with Proton-Donating Cations

Abstract: Isobutane and methane chemical ionization (CI) mass spectra of C-17a-epimeric, 17a-substituted 3-methoxyestra-1,3,5(10),8-tetraen-17a-ols and at C-17-epimeric 17-substituted 3-methoxyestra-1,3,5(10)-trien-17-ols, as well as of some their derivatives, have been studied. In each epimeric pair, the peak intensity ratio [MH-H(2)O](+) / [MH](+) is greater for stereoisomers having an axial (or quasi-axial) hydroxyl group. The same regularity in the peak intensity ratio [MH-CH(3)COOH](+) / [MH](+) is valid for acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…66 For example, the pronounced stereospecificity of ion-molecule reactions with proton-donating gas-reagents has been observed in the series of 17-and 17a-epimeric 17a-alkyl-17a-hydroxy-d-homo-estra-1,3,5(10),8-tetraenes, 17-alkyl-17-hydroxy-estra-1,3,5(10)-trienes and their acetates. 67 The observed quantitative differences between CI mass spectra of stereoisomers were explained by steric hindrance for the attack of proton-donating cations. Similar "approach control" was suggested to explain the stereospecificity of the protonation of tertiary alcohols in the transdecahydro-4-hydroxyquionoline series.…”
Section: Stereoisomersmentioning
confidence: 99%
“…66 For example, the pronounced stereospecificity of ion-molecule reactions with proton-donating gas-reagents has been observed in the series of 17-and 17a-epimeric 17a-alkyl-17a-hydroxy-d-homo-estra-1,3,5(10),8-tetraenes, 17-alkyl-17-hydroxy-estra-1,3,5(10)-trienes and their acetates. 67 The observed quantitative differences between CI mass spectra of stereoisomers were explained by steric hindrance for the attack of proton-donating cations. Similar "approach control" was suggested to explain the stereospecificity of the protonation of tertiary alcohols in the transdecahydro-4-hydroxyquionoline series.…”
Section: Stereoisomersmentioning
confidence: 99%
“…65 The results of CI-MS investigations on 17-substituted estra-and 17a-substituted-D-homoestra-derivatives have been reported. 66 Computational studies have shown that derivatives of tetrahydrochrisene (82) can be successfully docked into the second binding site of ERα and ERβ (Figure 8). …”
Section: Figurementioning
confidence: 99%